Governance and Design of Urban Infostructures: Analysing Key Socio-Technical Systems for the Vulnerability and Resilience of Cities - Wolfram, Marc; Vogel, Rico (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
Information, communication and knowledge creation are at the core of urban stakeholder interactions enabling the identification of vulnerabilities and the design of adequate responses to them. Urban infostructures play a crucial role within these processes, interfacing between a city’s ecological, social, technical, economic and political networks. Against this backdrop, this paper discusses the governance and design of urban infostructures from a socio-technical systems perspective. It, therefore, reviews pertinent technology components, as well as institutional and discursive frameworks and their respective influence on the identification and assessment of vulnerabilities and resilience building in cities. It concludes that approaches to developing urban infostructures should be a major concern when addressing urban resilience. There is a need to fully account for the hybrid character of urban infostructures as socio-technical systems, while also seizing opportunities for targeted transformation.
Keywords: Cities; Vulnerability; Resilience; Socio-technical systems; Local government; Information infrastructures; Spatial data infrastructures; Knowledge; Discourse